Evaluation of health service efficiency and effectiveness policy through performance based budgeting and quality control of health services: A literature review - Reynanda Sabrina; Assyifa Ramadhani; Robby Firmansyah; Riswandy Wasir (Indonesian Journal of Health Science, 2026)
The efficiency and effectiveness of health services represent one of the critical aspects in the management of public services, particularly in budget utilization and the implementation of health programs. Numerous studies indicate that performance-based budgeting and quality control of health services exert a significant influence on enhancing accountability as well as service quality within public service institutions. This literature review was conducted to evaluate the implementation of efficiency and effectiveness policies in health services through a performance-based budgeting approach and quality control of health services. The study employs a literature review method, with data sources obtained from Google Scholar and Garuda. The articles utilized are scientific journals addressing performance-based budgeting, service effectiveness, performance accountability, and quality control of health services. The findings of the review demonstrate that performance-based budgeting is capable of improving the effectiveness of service management and the accountability of public service institutions. Furthermore, quality control of health services, strengthening of reporting systems, and information technology support also contribute to the enhancement of service quality. Nevertheless, policy implementation continues to face several obstacles, including low human resource capacity, weak internal control mechanisms, and the suboptimal integration of reporting systems.